Wellness and Resiliency Plans for Special Educators Throughout the COVID-19 Global Pandemic and Beyond - Hunter, Elizabeth O'Neill; Hunter, Elizabeth M. Anderson (Journal of the American Academy of Special Education Professionals, 2024)
Special educators are among the countless professionals adversely impacted by the coronavirus (COVID-19) global pandemic. Before the pandemic, the special education profession was associated with increased occupational stress, anxiety, and job dissatisfaction. As we progress through the first post-pandemic school year, special educators continue to be adversely impacted by occupational demands associated with COVID-19. Here we discussed the basics of stress, the personal and professional implications of stress, and an examination of how to address this critical issue among these valuable professionals. We discussed the importance and development of wellness and resilience plans applied throughout the COVID-19 pandemic and beyond. The stress experienced by special educators is a significant occupational and ethical issue needing attention.